Non-parental carers’ role in the socio-emotional development of left-behind adolescents in transnational families - Panghulan, Abegail E.; Diano, Excel Josh S.
The study aims to identify the roles of the non-parental carers (NPCs) in nurturing the socio-emotional development (SED) of the left-behind adolescent (LBA) and analyze the factors that can hinder or facilitate them in performing these roles. 10 NPCs aged 25-77 years old residing in the National Capital Region and CALABARZON regions were interviewed about their experiences in caring for the LBA. Through thematic analysis, the roles of the NPC, facilitating and hindering factors to fulfilling their roles, and their strategies for addressing the hindering factors were identified and discussed. The results show that NPCs are emotional support providers and problem solvers to the LBA, and mediators between the LBA and their migrant parent. As they perform these roles, they encounter factors that can either facilitate or hinder their roles as NPCs. Of these factors, results show that positive attitudes and behaviors of LBA, attitudes of NPC towards LBA and positive interactions with other relatives are facilitating factors for the NPC’s role performance while negative attitudes and behaviors of LBA, peer interactions of LBA, generational differences, negative relationship with family members, and burnout are all negative factors that hinder the NPC. In the face of these hindering factors, the NPCs resorted to the following strategies: using disciplining techniques, seeking spiritual interventions, providing emotional support, sharing parenting responsibilities with migrant parents and other relatives, and showing vulnerability to LBA.